Automobile public transport in Kharkiv at the beginning of the twentieth century: projects and first attempts at implementation (based on materials from the local press) - Домановський, Андрій; Олешко, Наталя (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2020)
Research aim is to establish the history of the first projects and attempts to organize bus passenger transportation in Kharkov at the beginning of the twentieth century.Research methodology. The article discusses the emergence and development of bus traffic in Kharkiv at the beginning of the twentieth century from the point of view of the concept of modernization of urban space.Scientific novelty. For the first time in the historiography the history of bus traffic in Kharkiv at the beginning of the 20th century became a topic of a special scientific study. The basic facts of the organization of regular bus traffic in the city in the context of the state of transport communication at that time have been established.Conclusions. The publications of the newspapers «Yuzhnyj Kraj» («South Land») and «Utro» («Morning») make it possible to identify the causes and content of the first projects of automobile passenger transportation in the city, as well as to find out that the beginning of bus traffic was closely connected with the solution of the so-called «tram issue» horse-drawn railways, which belonged to Belgian owners. Certain projects for road transport of passengers in Kharkiv - suburban bus service along the route Kharkov Measurements and delivery of the public to the hippodrome from Teatralnaya Square during the days of equestrian competitions - were carried out already in 1908-1909, but for the first time an official bus service in the city was opened along a regular route from Veterinarnaya Street to the railway station on June 6, 1910. Bus traffic existed in Kharkov during the summer-autumn of 1910, was resumed in the spring of the following year and probably lasted no longer than until the autumn of 1911. The first experience of organizing bus passenger transportation in Kharkiv was not very successful and could not compete properly with other types of urban public transport of that time - horse and electric trams. The cost of bus transportation was too high compared to the cost of horse tram and city electric trams.